Response Time Perawat Berhubungan Dengan Kecemasan Pasien Di UGD Puskesmas Dinoyo Kota Malang - Sutriningsih, Ani; Ardiyani, Vita Maryah; Aryanti, Afifa Ramadani (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Patients in the emergency room (ER) often experience anxiety due to acute or severe pain, which may indicate a life-threatening condition, leading them to expect immediate treatment from nurses. Nurse response time plays a critical role in saving patients and has a direct impact on their anxiety levels. Patients who experience delays in receiving services from healthcare providers may feel afraid and worried about their condition. The aim of this research is to determine the relationship between nurse response time and patient anxiety in the ER at the Dinoyo Health Center, Malang City. The study employed a correlation research design using a cross-sectional approach. The population included all 50 patients in the ER, with a sample of 47 patients selected using systematic random sampling techniques. The independent variable was response time, while the dependent variable was patient anxiety. The instruments included response time observation sheets and the Hamilton Anxiety Rating Scale (HARS) questionnaire. Data were analyzed using the chi-square test. The results indicated that the majority of nurses exhibited good response times (70.2%), and the majority of patients reported no anxiety or were within the normal range (63.8%). A significant relationship was found between nurse response time and patient anxiety within p-value = 0.000 (0.05). Suggestions for future research include identifying patient anxiety levels in the ER based on factors such as the level of emergency, payment method, and availability of family assistance.